The queen of chess : how Judit Polgár changed the game - Wallmark, Laurie (Little Bee Books, 2023)
The queen of chess, Judit Polgar, dazzled the world as a prodigy, winning tournaments, gold medals, and defeating eleven world champions, including Garry Kasparov and Magnus Carlsen. At her peak, Judit was rated the eighth best chess player in the world.